WARMINGS IN THE FAR NORTHWESTERN PACIFIC PROMOTED PRE-CLOVIS IMMIGRATION TO AMERICA DURING HEINRICH EVENT 1 - Sarnthein M.; Kiefer T.; Elderfield H.; Grootes P.M.; Erlenkeuser H. (My University, 2006)
Well-dated multidecadal-to centennial-scale sediment records from the subarctic northwest Pacific show that the early deglacial 18.5-15.0 ka was marked by 3 pronounced short-term warmings of ~5 °C. They lasted 500-1500 yr each and were coeval with early to late stages of cold Heinrich event 1 in the North Atlantic. These regional climate windows may have promoted a pre-Clovis emigration of people from the cold-arid monsoon climate in East Asia to the climatically more favorable, then-emerged Beringian and Aleutian shelf regions and the Americas, as suggested by archeological findings. © 2006 Geological Society of America.
Keywords: HEINRICH I STADIAL; PALEOCEANOGRAPHY; PRE-CLOVIS IMMIGRATION; SEA-SURFACE WARMING; SUBARCTIC NORTH PACIFIC